Comparative study between the unit price compositions of the databases of the SINAPI, EMLURB and TCPO systems (Research, Society and Development, 2023)
The budget is the first means by which the costs of a work are known, and in it we must meet all the technical specifications defined in the project and the financial availability of the client. Among the main key points for obtaining a competitive budget value with the market, is the assembly of compositions of unitary price of services that adopt constructive techniques that reduce the consumption of material and the expense with labor, so that the final quality of service is not impaired. In this work, an analysis will be made of the difference in cost obtained by making 3 (three) budgets for the same single-family house using the different unit price compositions of the following databases: Sistema Nacional de Pesquisa de Custos e Índices da Construção Civil (SINAPI), Empresa de Manutenção e Limpeza Urbana do Recife (EMLURB) and the Tabela de Composições de Preços para Orçamento (TCPO) by editora Pini, with the objective of presenting and analyzing the possible factors that motivated the cost differences between the budgets, checking the items of each composition and their respective coefficients. At the end of the budget analysis, it was found that TCPO is the most conservative database, since it uses older construction techniques in unitary compositions, EMLURB brings costs based on outdated input prices and labor. And SINAPI presents CPUs with better construction techniques and more adapted to our current reality and with prices updated monthly.